Circadian Rhythm Effects on the Extraction and Identification of Semen on Semen-Stained Fabrics Using Seminal Fluid Biochemistry - Agoro, Eni-yimini; Alabrah, Peter; Amaihunwa, Kingsley (AlQalam Journal of Medical and Applied Sciences, 2024)
The rate of rape and other sexually induced crimes is rapidly on the increase worldwide with weak empirical confirmational tools, and expensive financial implications This is further compounded by poor proof of the time of the committal of the crime and its attendant effect on the parameter of interest. This called for a cheap and accurate approach involving the use of biochemical parameters indicative of seminal fluids on fabrics and other ancillary materials found in a crime scene. This study was therefore designed to validate a suitable seminal fluid biochemical approach to detecting seminal stained fabrics and the attendant circadian rhythm effects. Seminal fluid biochemical parameters used for the study include prostate-specific antigen, gamma-glutamyl transferase, acid phosphatase, magnesium, zinc, and inorganic phosphorus. These parameters were analyzed using WHO-approved methods after the extraction phase from dried stained fabrics. Forty (40) participants were recruited for the study divided into two groups; nocturnal and diurnal. The mathematical and empirical analysis data were analyzed using One-way ANOVA (Post Hoc) on an SPSS 25 version platform. The result showed a significant increase (p< 0.05) in seminal PSA, GGT, and ACP in the semen-stained fabrics when compared to distilled water-stained fabrics. In a similar vein, there was a significant increase in seminal ACP and PSA concentrations in the nocturnal group when compared to the diurnal, whereas seminal GGT decreased. In conclusion, this study has shown that semen-stained fabric can be detected for the presence of seminal fluids using seminal PSA, ACP, and GGT. Also, the effect of circadian rhythm should be considered during result interpretation. يتزايد معدل الاغتصاب وغيره من الجرائم ذات الدوافع الجنسية بسرعة في جميع أنحاء العالم مع ضعف أدوات التأكيد التجريبية، والآثار المالية الباهظة الثمن. ويتفاقم هذا الأمر بسبب ضعف الأدلة على وقت ارتكاب الجريمة وتأثيرها المصاحب على معيار الفائدة. وهذا يستدعي اتباع نهج رخيص ودقيق يتضمن استخدام المعايير البيوكيميائية التي تدل على وجود السوائل المنوية على الأقمشة والمواد المساعدة الأخرى الموجودة في مسرح الجريمة. لذلك تم تصميم هذه الدراسة للتحقق من صحة النهج البيوكيميائي المناسب للسائل المنوي للكشف عن الأقمشة الملطخة المنوية وتأثيرات إيقاع الساعة البيولوجية المصاحبة. تشمل المعلمات البيوكيميائية للسائل المنوي المستخدمة في الدراسة مستضد البروستاتا النوعي، ترانسفيراز جاما جلوتاميل، الفوسفاتيز الحمضي، المغنيسيوم، الزنك، والفوسفور غير العضوي. تم تحليل هذه المعلمات باستخدام الطرق المعتمدة من منظمة الصحة العالمية بعد مرحلة الاستخراج من الأقمشة الملونة المجففة. تم تجنيد أربعين (40) مشاركًا للدراسة مقسمين إلى مجموعتين؛ ليلية ونهارية. تم تحليل بيانات التحليل الرياضي والتجريبي باستخدام ANOVA أحادي الاتجاه (Post Hoc) على منصة الإصدار SPSS 25. أظهرت النتائج زيادة معنوية (p<0.05) في PSA وGGT وACP في الأقمشة الملوثة بالسائل المنوي مقارنة بالأقمشة الملوثة بالماء المقطر. وعلى نفس المنوال، كانت هناك زيادة كبيرة في تركيزات ACP وPSA المنوية في المجموعة الليلية بالمقارنة مع المجموعة النهارية، في حين انخفض GGT المنوي. في الختام، أظهرت هذه الدراسة أنه يمكن الكشف عن النسيج الملون بالسائل المنوي لوجود السوائل المنوية باستخدام PSA، ACP، وGGT. أيضا، ينبغي النظر في تأثير إيقاع الساعة البيولوجية أثناء تفسير النتائج.